Microvascular reconstruction for maxillofacial defects: a retrospective analysis of outcomes and complications in 121 consecutive cases - SeongRyoung Kim; Dong-Hun Lee; Kang-Min Ahn (SpringerOpen, 2020)
Abstract Background Microvascular reconstruction is the treatment of choice after oral cancer ablation surgery. There are few published studies of free flap survival among Korean populations. This study aimed to determine the survival rate after 121 consecutive cases of maxillofacial microvascular reconstruction and to analyze the complications associated with microsurgery. Methods This study included consecutive patients who underwent microsurgical reconstruction with free flaps, from January 2006 through September 2019, performed by a single surgeon at the oral and maxillofacial surgery department of a tertiary medical center. A total of 121 cases were reviewed retrospectively. The flap survival rate, flap type, radiotherapy history, complications, and treatment results were analyzed. Results Four different flap types were used for microvascular reconstruction: radial forearm (n = 65), fibula (n = 34), latissimus dorsi (n = 21), and serratus anterior muscle with rib bone free flap (n = 1). Total necrosis of the flap was found in four cases (two latissimus dorsi flaps and two fibular flaps). The free flap survival rate was 97.5%. Nineteen patients received radiotherapy before surgery, and none of them experienced flap failure. The mean operation time was 334 ± 83.1 min, and the mean ischemic time was 48.9 ± 12.7 min. Conclusions The success rate was reliable and comparable with previous studies. The success rate was not affected by radiation therapy. Free flaps can be safely used even after radiation treatment.